2002
DOI: 10.1046/j.1525-1314.2002.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of carbonaceous material in metasediments: a new geothermometer

Abstract: Metasedimentary rocks generally contain carbonaceous material (CM) deriving from the evolution of organic matter originally present in the host sedimentary rock. During metamorphic processes, this organic matter is progressively transformed into graphite s.s. and the degree of organisation of CM is known as a reliable indicator of metamorphic grade. In this study, the degree of organisation of CM was systematically characterised by Raman microspectroscopy across several Mesozoic and Cenozoic reference metamorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

55
1,503
4
19

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,015 publications
(1,581 citation statements)
references
References 47 publications
(68 reference statements)
55
1,503
4
19
Order By: Relevance
“…The D band is also called D1 band (Marques et al, 2009;Wopenka and Pasteris, 1993) or A band (Kelemen and Fang, 2001), and it originates in vibrations of the disordered structure of carbonaceous material (Beyssac et al, 2002(Beyssac et al, , 2003. The G band is assigned to vibrations of the ordered (graphitic) structure (Beyssac et al, 2002(Beyssac et al, , 2003. With increasing thermal maturity, these two bands show regular changes in their position, FWHM (full width at half maximum) and intensity, which have been shown to be clearly correlated with maturity (Guedes et al, 2010;Kelemen and Fang, 2001;Kostova et al, 2012;Quirico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The D band is also called D1 band (Marques et al, 2009;Wopenka and Pasteris, 1993) or A band (Kelemen and Fang, 2001), and it originates in vibrations of the disordered structure of carbonaceous material (Beyssac et al, 2002(Beyssac et al, , 2003. The G band is assigned to vibrations of the ordered (graphitic) structure (Beyssac et al, 2002(Beyssac et al, , 2003. With increasing thermal maturity, these two bands show regular changes in their position, FWHM (full width at half maximum) and intensity, which have been shown to be clearly correlated with maturity (Guedes et al, 2010;Kelemen and Fang, 2001;Kostova et al, 2012;Quirico et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, numerous papers have reported that the Raman spectral characteristics and related parameters of geological solid organic matter, including coals, carboniferous fossils and carbonaceous materials, can be used as indicators for thermal maturity (i.e., Beyssac et al, 2002;Ferrari and Robertson, 2000;Guedes et al, 2010;Kelemen and Fang, 2001;Kwiecinska et al, 2010;Muirhead et al, 2012;Quirico et al, 2005Quirico et al, , 2009Rahl et al, 2005;Roberts et al, 1995;Schopf et al, 2005;Schopf and Kudryavtsev, 2009;Zeng and Wu, 2007). Detailed studies have focused on coals with different rank (Green et al, 1983;Guedes et al, 2010;Kelemen and Fang, 2001;Marques et al, 2009;Quirico et al, 2005;Sonibare et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kelemen et al [12] and Liu et al [13] proposed a positive linear correlation between the inter-interval of peaks D/G and Ro. Beyssac et al [14,15] and Bernard et al [16] suggested that simple D/G band ratios are not adequate to evaluate the thermal maturity level of geologic carbonaceous materials by changes in Raman spectra. It seems that Raman spectra could be applied to evaluate the thermal maturity of carbonaceous materials, but that different reports have contradictory results and perspectives on the usefulness of different parameters.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In geology, the Raman signature of carboneous material can be used as a geothermometer. 12 The Raman signal allowed in the center of the Brillouin zone corresponding to the phase opposition motion of bonded atoms is degenerated. It is called G or E 2g mode.…”
Section: Introductionmentioning
confidence: 99%